Energy and economic performance of rooftop PV panels in the hot and dry climate of Iran. (10th February 2018) - Korsavi, Sepideh Sadat; Zomorodian, Zahra Sadat; Tahsildoost, Mohammad
Abstract: Photovoltaic (PV) Panels, one of the more promising renewable energy technologies, are growing rapidly nowadays, especially in developed countries. However, these systems have not achieved public acceptance in some countries due to low energy efficiency and poor economic performance, especially in countries which are subsidized in energy tariffs. In this paper, the energy and economic performance of fourteen rooftop PV systems with the power of 5 kW in the hot and dry climate of Iran are assessed by monitoring the total annual energy production and simulation. The monitored data is used to analyze systems' economic performance via Pay-Back Period (PBP), Net Present Value (NPV), Return of Investment (ROI) and Levelized Cost of Energy (LCOE). Results show that single array configuration systems have the maximum energy production while dividing the system decreases the production. Economic analysis shows that the average PBP is 11.6 years under actual price of electricity (0.21), however it is 46.9–50.5 years under subsidized average tariffs. ROI values range from 2.6 to 3.2 with the average of 2.9 for actual prices. Under subsidized prices, the cash generated by investment cannot even offset the costs that the investment requires during its lifetime with NCF and NPV being both negative. Overall, the systems are not economically beneficial under subsidized average tariffs in Iran, which discourages private and public sectors to investment on these systems. Environmentally, each PV system can averagely reduce 500 kg CO2 emission in the first year of installation and fourteen of them can approximately reduce 1, 613, 900 kg of CO2 emission during life time of PV panels. Highlights: Energy, economic and environmental performance evaluation of rooftop PV panels in 14 schools. Maximum electricity generation in single array configuration due to the lower shaded panels. Each system can averagely reduce 500 kg CO2 emission in first year of installation. PV systems are inconvenient under subsidized average tariffs while profitable for the state. This study discusses policies which make PV panels more economically viable.